PRIMA 2014: Principles and Practice of Multi-Agent Systems 17th International Conference, Gold Coast, QLD, Australia, December 1-5, 2014, Proceedings - Dam, Hoa Khanh; Pitt, Jeremy; Xu, Yang.; Governatori, Guido; Ito, Takayuki; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 17th International Conference on Principles and Practice of Multi-Agent Systems, PRIMA 2014, held in Gold Coast, QLD, Australia, in December 2014. The conference was co-located with the 13th Pacific RIM International Conference on Artificial Intelligence, PRICAI 2014. The 21 revised full papers presented together with 15 short papers were carefully reviewed and selected from 77 submissions. The papers are organized in topical sections on self organization and social networks/crowdsourcing; logic and argumentation; simulation and assurance; interaction and applications; norms, games and social choice; and metrics, optimisation, negotiation and learning.
Self Organization and Social Networks/Crowdsourcing -- Logic and Argumentation -- Simulation and Assurance -- Interaction and Applications -- Norms, Games and Social Choice -- Metrics, Optimisation, Negotiation and Learning.
Keywords: Artificial intelligence; Software engineering; User interfaces (Computer systems).; Human-computer interaction; Information storage and retrieval systems; Electronic commerce; Application software; Artificial Intelligence; Software Engineering; User Interfaces and Human Computer Interaction; Information Storage and Retrieval; e-Commerce and e-Business.; Computer and Information Systems Applications